Presurgical Screening Improves Risk Prediction for Delirium in Elective Surgery of Older Patients: The PAWEL RISK Study - Eschweiler, Gerhard W.; Czornik, Manuel; Herrmann, Matthias L.; Knauer, Yvonne P.; Forkavets, Oksana; von Arnim, Christine A. F.; Denkinger, Michael; Küster, Olivia; Conzelmann, Lars; Metz, Brigitte R.; Maurer, Christoph; Kentischer, Felix; et al. (Frontiers in Aging Neuroscience, 2021)
Introduction: The number of elective surgeries in patients over 70 years is continuously growing. At the same time, postoperative delirium (POD) is common in older patients (5-60%) depending on predisposing risk factors such as multimorbidity, cerebral disease or cognitive state and precipitating factors such as duration of surgery. Knowledge about individual risk profiles prior to elective surgery may help to identify patients at increased risk for the development of POD. In this study, clinical and cognitive risk factors for POD were investigated in patients undergoing various elective cardiac and non-cardiac surgeries. Methods: The PAWEL study is a prospective, interventional trial on delirium prevention. At baseline, 880 inpatients at 5 surgical centers were recruited for the sub-sample PAWEL-R. Multimodal assessments included clinical (renal function, medication, American Society of Anesthesiologists Physical Status Classification System (ASA)), geriatric and cognitive assessments, which comprised the Montreal Cognitive Assessment Scale (MoCA), Trail-making Test and Digit Span backwards. Delirium incidence was monitored postoperatively by the Confusion Assessment Method (CAM) and a chart review for up to one week or until discharge. Multivariate regression models and Chi-square Automatic Interaction Detectors (CHAID) analyses were performed using delirium incidence as the primary outcome. Results: 18 risk factors were investigated in elective cardio-vascular and orthopedic or general surgery. A total of 208 out of 880 patients (24%) developed POD. A global regression model including all risk variables predicted delirium incidence with high accuracy (AUC = 0.81; 95%-CI [0.77, 0.85]). A simpler model (clinical and cognitive variables; model CLIN-COG) of 10 factors only including surgery type, multimorbidity, renal failure, polypharmacy, ASA, cut-to-suture time and cognition (MoCA, digit span backwards and preexisting dementia) only, however, exhibited similar predictive accuracy (AUC = 0.80; 95%-CI [0.76, 0.84]). Conclusion: The risk to develop a POD can be estimated by preoperative assessments such as ASA classification, expected cut-to-suture time and short cognitive screenings. This rather efficient approach predicted POD risk over all types of surgery. Thus, a basic risk assessment including a cognitive screen can help to stratify patients at low, medium or high POD risk to provide targeted prevention and/or management strategies for patients at risk.